Double Heterozygous Mutations Involving Both HNF1A/MODY3 and HNF4A/MODY1 Genes: A case report - Forlani, Gabriele (American Diabetes Association, 2010)
OBJECTIVE: We describe a maturity-onset diabetes of the young (MODY) case with mutations involving both HNF4A and HNF1A genes. RESEARCH DESIGN AND METHODS: A male patient was diagnosed with diabetes at age 17; the metabolic control rapidly worsened to insulin requirement. At that time no relatives were known to be affected by diabetes, which was diagnosed years later in both the parents (father at age 50 years, mother at age 54 years) and the sister (at age 32 years, during pregnancy). RESULTS: The genetic screening showed a double heterozygosity for the mutation p.E508K in the HNF1A/MODY3 gene and the novel variant p.R80Q in the HNF4A/MODY1 gene. The genetic testing of the family showed that the father carried the MODY3 mutation while the mother, the sister, and her two children carried the MODY1 mutation. CONCLUSIONS: MODY1 and MODY3 mutations may interact by chance to give a more severe form of diabetes (younger age at presentation and early need of insulin therapy to control hyperglycemia).